2002
DOI: 10.1271/bbb.66.2449
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of Fluorescein in Caco-2 Cell Monolayers and Use of Such Transport inIn VitroEvaluation of Phenolic Acid Availability

Abstract: Fluorescein is a marker-dye customary applied to the evaluation of tight-junctional permeability of epithelial cell monolayers. However, the true mechanism for the permeation has not been elucidated. Transepithelial transport of fluorescein in Caco-2 cell monolayers was therefore examined. Fluorescein transport was dependent on pH, and in a vectorical way in the apical-basolateral direction, but it was independent of the tight-junctional permeability of monolayers of these human intestinal cells. The permeatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 37 publications
8
87
0
Order By: Relevance
“…This result is in good agreement with the distribution study and the results shown in Figure 4 and 5, showing that FTA was mainly permeated via paracellular diffusion. LY, a marker compound for paracellular transport, also showed this trend [24] . Figure 6 summarises the permeability coefficients of FTA in the absence and presence of inhibitors.…”
Section: The Paracellular Transport Of Fta Across the Caco-2 Cell Monmentioning
confidence: 81%
“…This result is in good agreement with the distribution study and the results shown in Figure 4 and 5, showing that FTA was mainly permeated via paracellular diffusion. LY, a marker compound for paracellular transport, also showed this trend [24] . Figure 6 summarises the permeability coefficients of FTA in the absence and presence of inhibitors.…”
Section: The Paracellular Transport Of Fta Across the Caco-2 Cell Monmentioning
confidence: 81%
“…Small water-soluble molecules, such as water and lucifer yellow permeate the Caco-2 cell monolayer via the paracellular pathway. 11) To investigate the absorption route of myricitrin, we incubated the Caco-2 cell monolayer with various TEER values in a solution containing 100 mM of myricitrin and lucifer yellow in the apical side (Fig. 1).…”
mentioning
confidence: 99%
“…17,19) MCTmediated transport of phenolic acids was first determined by this method. [4][5][6] The MCT isoform responsible for fluorescein transport is presumed to be identical to that responsible for the transport of phenolic acids in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…ferulic acid or p-coumaric acid) have shown lactic acid, which is a typical substrate for MCT1-MCT4, to have no effect on their transport. 4,5,17) Thus, it was tentatively proposed that Caco-2 intestinal cells might possess a novel MCT responsible for phenolic acid transport which is distinct from MCT1-MCT4. The results described in this paper confirm this proposal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation